2020
DOI: 10.1177/1359105320934192
|View full text |Cite
|
Sign up to set email alerts
|

Identification of risk for posttraumatic stress disorder symptom clusters early after trauma

Abstract: The current study examined how the injured trauma survivor screen (ITSS), a hospital-administered screener of posttraumatic stress disorder (PTSD) and depression, differentially predicted PTSD symptom cluster severity. Participants from a Level 1 trauma center ( n = 220) completed the ITSS while inpatient and PTSD symptoms were assessed one-month post discharge. Perceived life threat and intentionality of injury were key predictors of avoidance, re-experiencing, and hyperarousal symptom clusters. However, nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…overestimating the probability of future harm) and from poor elaboration or contextualization of the trauma memory. The findings fit with earlier studies showing that perceived life threat is a predictor of PTSD symptoms (Giannoni-Pastor, Eiroa-Orosa, Fidel Kinori, Arguello, & Casas, 2016;Kassam-Adams et al, 2009;Timmer-Murillo et al, 2020), and that peri-traumatic processes indirectly affect long-term PTSD symptoms through acute PTSD symptoms (Engelhard, van den Hout, Kindt, Arntz, & Schouten, 2003).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…overestimating the probability of future harm) and from poor elaboration or contextualization of the trauma memory. The findings fit with earlier studies showing that perceived life threat is a predictor of PTSD symptoms (Giannoni-Pastor, Eiroa-Orosa, Fidel Kinori, Arguello, & Casas, 2016;Kassam-Adams et al, 2009;Timmer-Murillo et al, 2020), and that peri-traumatic processes indirectly affect long-term PTSD symptoms through acute PTSD symptoms (Engelhard, van den Hout, Kindt, Arntz, & Schouten, 2003).…”
Section: Discussionsupporting
confidence: 89%
“…When life threat is not appraised as a time-limited event and with global negative implications, it may maintain PTSD symptoms (Ehlers & Clark, 2000). Although one study found no association between perceived life threat of partners and close relatives with acute PTSD symptoms (Bond et al, 2017), a larger body of evidence points towards a detrimental impact of life threat in PTSD occurrence after injury (Timmer-Murillo, Hunt, Geier, Brasel, & deRoon-Cassini, 2020). Therefore, it is hypothesized that perceived life threat predicts more PTSD symptoms in partners.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the current study, main effects demonstrated that those who endorse life threat had higher PTSD symptoms across all four symptom clusters compared with those who did not experience life threat. As such, life threat appears to be a stable risk factor in predicting PTSD development including within traumatically injured populations and should be evaluated during hospitalization 22,26 . Similarly, main effects of trauma type showed that individuals who experienced assaultive traumas endorsed higher reexperiencing, hyperarousal, and avoidance symptoms relative to nonassaultive traumas.…”
Section: Discussionmentioning
confidence: 99%
“…The ITSS PTSD items demonstrate good sensitivity (75%) and specificity (93.94%) 3 . For the purpose of this study, one item assessing perceived life threat during the trauma (i.e., “did you think you were going to die?”) was used 5,9,10,12,26 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation